Dealing with adult L2 learners: A study of the issues concerning e-PJJ students in UiTM (northern region) / Suhardi Wan Mansor …[et al.] - Wan Mansor, Suhardi; Dourado, Rita Maria; Yew Fong, Law (Research Management Institude, 2005)
This study sets out to look at the issues concerning E-PJJ programme conducted at UiTM branch campuses of the Northern Region (Kedah, Perlis and Perak). The issues being looked into cover the demands of an e-PJJ programme for adult students and the problems they face, the readiness factor, whether they (the adult learners) are ready for this type of programme. The issues of being internet savvy and factors involving adults learning a second language are also being investigated. Data gathered through questionnaires correspond to the issues and the findings showed that about half the total amount of students were ready for the demands of this type of programme. The findings also showed that the forum (web page) was not fully utilized and due to factors like unavailability to the facility and lack of knowledge of using it. When it comes to learning English a majority of the adult learners confessed that they are not conversant in the language and have difficulty using it. Although the study was on a very small scale it provides useful insights and further research in this area on a very much larger scale ought to be explored to allow for better generalization to be made in planning a distance learning programme. The recommendations for this study are also included for further research and use.